The City-Idea in Argentina: a study in evanescence - Morse, Richard M. (Revista de História, 1975)
Within the current flood of scholarship on cities flows a modeststream of studies in quest of subjacent, comprehensive meanings: thecity as idea, as image, as metaphor. In approaching the present thispursuit of the city-idea requires increasing ingenuity, for nowadaysthe "city" is fast disappearing.